DEVELOPING LATVIAN TERMINOLOGY OF TRANSLATION STUDIES: THE FIRST STEPS - Sīlis, Jānis (Vertimo studijos, 2017)
The rapidly increasing number of translatological publications in the Latvian language, as well as the necessity to read theoretical courses in Latvian, which is the common language for Master-level students majoring in translation with different working languages, makes a compilation of an Explanatory Dictionary of Latvian Terminology of Translation Studies a topical issue. The article gives a brief insight into the first step that has up to now been taken in this direction, characterising creators and users of terms in the contemporary world, providing an overview of Translation Studies research in Latvia, listing the general characteristics of the terminology of Translation Studies, explaining the procedure of term approval in Latvia, familiarising the readers with the existing core set of translatological terms, providing the author’s suggestions concerning the enlargement of the list of Latvian translatological terms with the goal to select’ longlivers’ and avoid ’ephemera’.